Lifting the Veil: Drawing insights about design teams from a cognitively-inspired computational model. (September 2015) - McComb, Christopher; Cagan, Jonathan; Kotovsky, Kenneth
Abstract : Novel design methodologies are often evaluated through studies involving human designers, but such studies can incur a high personnel cost. It can also be difficult to isolate the effects of specific team or individual characteristics. This work introduces the Cognitively-Inspired Simulated Annealing Teams (CISAT) modeling framework, a platform for efficiently simulating and analyzing human design teams. The framework models a number of empirically demonstrated cognitive phenomena, thus balancing simplicity and direct applicability. This paper discusses the model's composition, and demonstrates its utility through simulating human design teams in a cognitive study. Simulation results are compared directly to the results from human designers. The CISAT model is also used to identify the most beneficial characteristics in the cognitive study. Highlights: This work introduces a computational framework for modeling engineering design teams. This framework incorporates various empirically demonstrated psychological phenomena. The framework also enables detailed analysis of each cognitive phenomenon. When used to model the results of a cognitive study, major trends are reproduced. Analysis within the framework shows the possible benefit of weak bonds in teams.